Lead user method vs. innovation contest: An empirical comparison of two open innovation methodologies for identifying social innovation for flood Resilience in Indonesia - Moritz Goeldner; Daniel J. Kruse; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2017)
Organizations in the humanitarian sector often face problems that are hard to solve owing to their complexity and high hidden solution knowledge. We investigate two problem-solving governance mechanisms in the case of floods in Indonesia. In our study, we compare the costs and benefits of two open innovation tools for identifying social innovation: an innovation contest and the lead user method. An innovation contest is a challenge among participants, who submit potential solutions to a problem that is posted in an open call. In contrast, the lead user method is a structured search process to identify innovators who have already developed solutions for their own needs or those of their peers. While innovation contests have seen significant attention, there is very little evidence that the lead user method is a suitable tool to identify social innovation. In our study, the contest yielded more than twice as much submissions as the lead user method (60 vs. 25). Our analysis reveals that concepts obtained by the lead user method score significantly higher in overall quality as well as regarding use value, feasibility, degree of elaboration, and social impact. The concepts' novelty do not significantly differ between the two groups. We discuss these findings against the background of the humanitarian sector being torn between capacity overload and the need to overcome a one-size-fits-all approach. By transferring two recognized governance forms for innovation identification from the private sector to the humanitarian sector, we introduce a new path towards empowering local innovators to solve humanitarian challenges.
Keywords: 330